El desarrollo del pensamiento lógico con sus procesos de enseñanza aprendizaje - Icaza Hidalgo, Harry Fernando (2015)
learning processes respond to an anthropological issue in which the human being is considered as a bio-psycho-logical being. Especially highlighting the logical aspect, as she responds to "think straight" and not just to how to think. This work has three approaches: philosophical as far spoken of as the science of logical reasoning and which the first chapter is devoted through a brief historical overview, the second approach is psychological in terms of development process the person especially in the cognitive domain, related to the development of thought, and finally in the pedagogical approach that examines how pedagogy relates to thought, in the third chapter, how thought is applied in everyday making this development a significant learning through some key elements in the fourth chapter will deepen the practical application in some problems arising in educational work proposing characteristics for the teacher can assume them and apply them in the educational process of students.